Myocardial Uptake of Iodinated Free Fatty Acids and 201T1 in Experimental Ischemia - Westera, G.; van der Wall, E. E.; Visser, F. C.; Scholtalbers, A. S.; Eenige van, M. J.; Roos, J. P. (Nuklearmedizin - NuclearMedicine, 1984)
In an experimental study, we evaluated the uptake of (131I)-17-iodo heptadecanoic acid (131I-HDA), (125I)-15-4 (4-iodophenyl) pentadecanoic acid (125I-PPA) and thallium-201 (201T1) in the dog heart. Twenty dogs were studied and divided into 3 groups: in group A, 10 dogs (4 normal, 6 with coronary artery occlusion) were studied with 131I-HDA and 201T1; in group B, 5 dogs (with occlusion) received 125I-PPA and 201T1; and in group C, 5 dogs (with occlusion) were studied with 125I-PPA and 131I-HDA. Two min after administration of the compounds the hearts were excised and stored in formaldehyde. After sectioning of the left ventricle, total uptake was counted and expressed in percentage of injected dose. Uptake in the normal myocardium (group A) was 4.2 ±0.6% for 131I-HDA and 4.6 ±0.7% for 201T1; in the occluded dog hearts (group A) we measured values of 2.6 ±0.4% for 131I-HDA (p<0.001) and 3.4 ±0.6% for 201T1 (p<0.01). Uptake of 131I-HDA, 125IPPA and 201T1 in groups B and C was not significantly different: group B, 125I-PPA 2.8 ±0.8% and 201T1 ± 0.5%; group C, 125I-PPA 1.9 ±0.7% and 131I-HDA 1.6 ±0.6%. Moreover, regional distribution of both iodinated fatty acids was quite comparable with the distribution of 201T1. We conclude that 131I-HDA and 125I-PPA show similar uptake as 201T1 and are distributed according to coronary artery perfusion, which underscores their value as myocardial imaging agents.